Functional role of PLCE1 intronic insertion variant associated with susceptibility to esophageal squamous cell carcinoma. (2nd November 2017) - Wei, Lixuan; Shao, Mingming; Zhao, Yanjie; Zheng, Jian; Chu, Jiahui; Chang, Jiang; Cheng, Xinxin; Cui, Qionghua; Peng, Linna; Luo, Yingying; Tan, Wenle; Tan, Wen; et al.
Abstract : This study identifies a four-base insertion/deletion variation in the intron of the PLCE1 gene that impairs PLCE1 transcription via a long-range regulatory mechanism. The attenuated PLCE1 expression due to the genetic variant may contribute to susceptibility to ESCC. Abstract: Genome-wide association studies (GWAS) have consistently identified PLCE1 as esophageal squamous cell carcinoma (ESCC) susceptibility gene; however, the functional role of PLCE1 variants remains to be verified. In this study, we performed fine mapping of the PLCE1 region using our previous ESCC GWAS data and identified 33 additional risk variants in this susceptibility locus. Here, we report the functional characterization of a four-nucleotide insertion/deletion variation (rs71031566 C----/CATTT) in PLCE1 that was associated with risk of developing ESCC. We demonstrate for the first time that rs71031566[CATTT] insertion creates a silencer element, repressing PLCE1 transcription via long-range interaction with PLCE1 promoter mediated by OCT-2 binding. PLCE1 is down-regulated in majority of clinical ESCC samples and overexpression of PLCE1 in ESCC cells suppresses cell growth in vitro and in vivo, suggesting a tumor suppressor role of this gene. Therefore, repression of PLCE1 transcription may be the underlying mechanism for the rs71031566[CATTT] variant to be susceptible to ESCC.